Flame retardant, antimicrobial, and mechanical properties of multifunctional polyurethane nanofibers containing tannic acid-coated reduced graphene oxide - Young Nam Kim (Elsevier, 2021)
Graphene nanoparticles coated with tannic acid were synthesized as non-halogen flame retardants; further, these nanoparticles were electrospun with polyurethane to produce multifunctional composite nanofibers. The composite nanofibers showed improved flame retardant, antimicrobial, and mechanical properties with increasing amounts of bio-based, non-halogen flame retardant. For instance, at 5 wt% of flame retardant, the peak heat release rate was reduced from 340.75 to 235.23 W/g along with 500% and 135% improvement in the antimicrobial activity and Young's modulus, respectively, compared to neat polyurethane fibers. These multifunctional composite nanofibers have potential applications in various fields, such as automobile, construction, and biomedical device.